THE JOSEPH SAGA: TURNABOUTS, TRADE-OFFS, AND TRANSIENCE. Issue 62 (2022) - Cahn, Steven M.
Abstract : Using the biblical saga of Joseph as an example, I maintain that turnabouts, trade-offs, and transience are endemic to the human condition.